Kerusakan Histologi Insang Ikan Sapu-sapu (Pterygoplichthys pardalis) setelah Paparan Merkuri (HgCl2) - Siti Anikha Idzni; Diah Wulandari Rousdy; Junardi Junardi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Mercury is a heavy metal that can undergo biomagnification in the tissue of aquatic organisms, including accumulating in the gills of fish. The main accumulation of mercury occurs in organisms that live in polluted waters, one of which is the suckermouth cat fish (Pterygoplichtys pardalis). The purpose of this study was to determine the histological damage of Pterygoplichtys pardalis gills against mercury (HgCl2) exposure. This study used a Completely Randomized Design consisting of six treatments and three replications. The treatments consisted of control; 0.01 0.02; 0.04; 0.08; 0.16 ppm HgCl2 concentration. The results of the study obtained forms of gill damage in the form of edema, hyperplasia, lamella fusion and epithelial lifting. The highest level of damage occurred at 0.16 ppm HgCl2 concentration in the form of a reduction in secondary lamella structure. Exposure to mercury causes damage to P. pardalis fish gills